Antimicrobial Resistant Escherichia coli in Sub-Urban Community of Kathmandu Valley - Tiwari, Bishnu Raj; Adhikari, Rajan Prasad (Tribhuvan University Journal, 2011)
Available with full text Key words: Antimicrobial Resistant; Water; Chicken faeces; E.coli Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 65-72 Uploaded date: 21 April, 2011